Gene promoters dictate histone occupancy within genes. (6th September 2013) - Perales, Roberto; Erickson, Benjamin; Zhang, Lian; Kim, Hyunmin; Valiquett, Elan; Bentley, David
<x xml:space="preserve">Abstract</x> Spt6 is a transcriptional elongation factor and histone chaperone that reassembles transcribed chromatin. Genome‐wide H3 mapping showed that Spt6 preferentially maintains nucleosomes within the first 500 bases of genes and helps define nucleosome‐depleted regions in 5′ and 3′ flanking sequences. In Spt6‐depleted cells, H3 loss at 5′ ends correlates with reduced pol II density suggesting enhanced transcription elongation. Consistent with its 'Suppressor of Ty' (Spt) phenotype, Spt6 inactivation caused localized H3 eviction over 1–2 nucleosomes at 5′ ends of Ty elements. H3 displacement differed between genes driven by promoters with 'open'/DPN and 'closed'/OPN chromatin conformations with similar pol II densities. More eviction occurred on genes with 'closed' promoters, associated with 'noisy' transcription. Moreover, swapping of 'open' and 'closed' promoters showed that they can specify distinct downstream patterns of histone eviction/deposition. These observations suggest a novel function for promoters in dictating histone dynamics within genes possibly through effects on transcriptional bursting or elongation rate.